Characteristic of Head Injury Patients Admitted to Intensive Care Unit in Dr. Mohammad Hoesin Palembang General Hospital - Ferdi Stefiyan; Trijoso Permono (Sriwijaya Journal of Surgery, 2021)
Introduction: Head injury is both major health and socioeconomic problem worldwide. Epidemiological studies of head injuries are essential for the effective prevention and treatment of head injury patients, but often found with unclear definitions of head injury. The use of the ICU is associated with higher costs and decreased availability for patients who need it. Oftenly, patients with head injuries require admission to the ICU both before surgery and after surgery. We aim to describe the charachteristic of patients with head injuries who were admitted to the emergency department (ED) and treated in the ICU at Mohamad Hoesin Hospital Methods: This research was an observational descriptive study. Using secondary data from the medical records of Mohammad Hoesin Hospital, Palembang. Performed in the from July 2019 to December 2019. Samples were all patients diagnosed with head injuries. Results: There were 177 subjects participated who met study critera, of which 51 subjects were admitted to ICU. ICU-admitted head injured patients were mostly male (78.5%). The largest age distribution is 11-20 year old (33.3%). The most common type of head injuries admitted to ICU according to CT scan was hemorrhagic head injuries (88.9%). The most common type of head injury admitted to ICU according to GCS was severe head injury (51.1%) Conclusion: Male patients, patients age of 11–20-year-old, severe head injury, and hemorrhagic head injury were the most common characteristic of patients diagnosed with head injuries admitted to ICU at Mohammad Hoesin Hospital